Atlas of Fetal Ultrasound Normal Imaging and Malformations - Bunduki, Victor (Springer International Publishing, 2018)
The present book is an illustrated guide on fetal medicine, including a wealth of normal and pathological/malformations ultrasound images, throughout the whole pregnancy. Thus, the book intends to fill two gaps in once: The lack of a material discussing the basic principles of fetal ultrasound, which are the basement for a more efficient learning in fetal medicine. . The need for a thorough approach in fetal medicine, presenting both normal and pathological imaging, allowing a detailed evaluation of clinical conditions of importance in prenatal care and follow up. The Atlas of Ultrasound Imaging is an up to date guide to all obstetricians, gynecologists and pediatricians who intend to upgrade their knowledge in fetal medicine, as well as to any other professional, professor, student or research interested in fetal ultrasound. .